High-efficiency environment-friendly low-temperature gel breaker for shallow oil and gas well and use method thereof
By using a debonding agent system with persulfate and sodium thiosulfate under low temperature conditions, combined with redox catalysis and self-heating reaction, the problem of difficult to crack polyacrylamide fracturing fluid at low temperatures in the prior art is solved, and an efficient and environmentally friendly debonding effect is achieved.
Patent Information
- Application Number
- CN202510336491.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The prior art is difficult to effectively crack polyacrylamide fracturing fluid under low temperature conditions of 10~50°C, resulting in large amounts of cracking agents, high cost and easy contamination of reservoirs.
The low-temperature cracker system is used to activate the persulfate, sodium thiosulfate, sodium bisulfate formaldehyde solution, chelating agent, sodium nitrite, ammonium chloride and catalytic sustained-release capsules, and the persulfate is activated through redox catalytic effect and self-heating reaction to generate free radicals to destroy the polymer chain.
It achieves efficient cracking of fracturing fluid under low temperature conditions, reduces the amount of glue breaker, ensures the maintenance of viscosity during construction, and avoids heavy metal ion pollution, achieving the purpose of environmental protection, pollution-free and increased production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemicals for oil and gas well fracturing, and in particular to a high-efficiency, environment-friendly, low-temperature gel breaker for shallow oil and gas wells and a use method thereof. Background Art
[0002] Hydraulic fracturing is a commonly used process to increase the production of oil and gas wells. During the fracturing construction process, fracturing fluid needs to be injected into the formation. Its main purposes are: (1) low filtration and low friction fracturing fluid is squeezed into the formation to form cracks; (2) fracturing fluid with a certain viscosity carries proppant into the cracks to form effective support and thus form a good diversion channel; after the fracturing construction, the fracturing fluid that has entered the well needs to be degelled to avoid clogging the cracks and polluting the reservoir.
[0003] Currently, the commonly used fracturing fluid thickeners are mainly guar gum and polyacrylamide. Among them, the polymer fracturing fluid system based on polyacrylamide has strong C=C bond binding force. It is difficult and costly to break the gel in low-temperature wells of 10~50℃ represented by coalbed methane and shallow oil and gas wells, which has always been a technical problem in oil and gas field development.
[0004] Currently, commonly used breakers include bio-enzyme breakers and peroxide breakers. Bio-enzyme breakers are mainly used for breaking guar gum-based fracturing fluids. At the same time, the activity of bio-enzymes is greatly affected by temperature and pH value, and the cost is high, making it difficult to apply them on a large scale and in a targeted manner. Peroxides such as persulfate and hydrogen peroxide currently have a relatively good breaking effect above 50°C and are widely used. However, when the temperature is below 50°C, the ambient temperature is not enough to provide the energy required for persulfate to generate oxygen free radicals, resulting in a significant weakening of the breaking ability of the persulfate breaker, and the purpose of breaking the gel cannot be achieved.
[0005] At 10~50℃, the oxidant-based gel breaking system needs to add a gel breaking activator so that the oxidant can release oxygen free radicals at low temperature, destroy the main chain structure of the polymer, and achieve the purpose of gel breaking; according to the currently disclosed patent technology, low-temperature gel breaking activators all contain copper salts, iron salts, zinc salts, silver ions, etc., and these activators inhibit the expansion of polyacrylamide molecular chains, which leads to difficulty in increasing the viscosity of the fracturing fluid or rapid viscosity reduction, and cannot meet the viscosity maintenance requirements during construction. At the same time, such substances are easy to form precipitation and complexes in the formation, seriously polluting the reservoir. In recent years, major oil fields have restricted the entry of such substances into the well; the currently commonly used reducing agents have low activity at low temperatures, slow gel breaking speed, and large dosage. Therefore, we need to develop a more efficient low-temperature activation system that has the beneficial effects of reducing the dosage of persulfate and activator, increasing the gel breaking rate of the fracturing fluid in low-temperature wells, and ensuring the construction viscosity and heavy metal ions without polluting the formation, so as to achieve the purpose of environmental protection, pollution-free, and increased production. Summary of the invention
[0006] The purpose of the present invention is to provide a high-efficiency and environment-friendly low-temperature gel breaker for shallow oil and gas wells and a method of using the same, so as to solve the problems existing in the prior art.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: A high-efficiency and environment-friendly low-temperature gel breaker for shallow oil and gas wells, wherein the high-efficiency and environment-friendly low-temperature gel breaker for shallow oil and gas wells is prepared by uniformly mixing, by weight, 0.4-0.5 parts of persulfate, 0.075-0.12 parts of sodium thiosulfate, 0.3-0.375 parts of sodium bisulfite formaldehyde solution, 0.003-0.0075 parts of chelating agent, 8-9 parts of sodium nitrite, 6-7 parts of ammonium chloride, 0.8-1 parts of catalytic sustained-release capsules, and 40-50 parts of pure water; The chelating agent is glucose; The catalytic sustained-release capsule is prepared by reacting glutaraldehyde with sodium carboxymethyl cellulose, adding the reacted glutaraldehyde to the sustained-release capsule core, impregnating the core with the glutaraldehyde, and drying the resulting capsule. The sustained-release capsule core is prepared by polymerizing acrylic acid, acrylamide, sodium lignin sulfonate, polyvinyl alcohol, and a cross-linking agent and then loading oxalic acid; The cross-linking agent is N,N'-methylenebisacrylamide.
[0008] As an optimization, the persulfate is one of ammonium persulfate, potassium persulfate, and sodium persulfate.
[0009] As an optimization, the sustained-release capsule core is prepared according to the following process: 1-1.2 parts of polyvinyl alcohol and 40-50 parts of pure water are mixed uniformly by mass, stirred at 85-90°C and 300-400r / min for 50-60min until dissolved, cooled to 50-60°C, 1-1.2 parts of sodium lignin sulfonate and 0.2-0.4 parts of ammonium persulfate are added, stirring is continued for 30-40min, 4-6 parts of oxalic acid, 80-90 parts of acrylic acid mixed solution, continue stirring for 30-40 minutes, add 0.04-0.06 parts of N,N'-methylenebisacrylamide, heat to 70-75℃, stir at 300-400r / min for 4-5 hours, vacuum dry at 60-70℃ for 18-20 hours, soak and wash with ethanol 3-4 times, vacuum dry at 60-70℃ for 5-6 hours, crush and pass through a 40-50 mesh sieve to obtain a sustained-release capsule core.
[0010] As an optimization, the acrylic acid mixed solution is obtained by mixing 20-30 parts of acrylic acid and 50-60 parts of 3 mol / L sodium hydroxide solution by mass, adding 2-3 parts of acrylamide, and stirring at 200-300 r / min at room temperature until completely dissolved.
[0011] As an optimization, the catalytic sustained-release capsules are prepared according to the following process: by mass, in a 50-60°C water bath, 50-100 r / min, 2-3 parts of 1wt% glutaraldehyde aqueous solution are added to 50-60 parts of 3wt% sodium carboxymethyl cellulose aqueous solution at a rate of 2-3 drops per second, and stirring is continued for 5-6 hours after the addition is completed, and the mixture is naturally cooled to room temperature. Under stirring conditions of 50-100 r / min, 2-3 parts of sustained-release capsule cores are added thereto and immersed for 20-30 minutes, and the mixture is taken out and vacuum dried at 60-70°C for 16-18 hours to obtain catalytic sustained-release capsules.
[0012] As an optimization, the mass fraction of the sodium bisulphite formaldehyde solution is 35%.
[0013] As an optimization, the model of the polyvinyl alcohol is PVA1788.
[0014] As an optimization, the model of the sodium lignin sulfonate is sodium lignin sulfonate-M03, which was purchased from Shanghai Tingruo Chemical Co., Ltd.
[0015] As an optimization, the model of the sodium carboxymethyl cellulose is FVH9, which is purchased from Shanghai Changguang Enterprise Development Co., Ltd.
[0016] A method for using an efficient and environmentally friendly low-temperature gel breaker for shallow oil and gas wells in petroleum fracturing fluid. The efficient and environmentally friendly low-temperature gel breaker for shallow oil and gas wells is added to the fracturing fluid at a mass fraction of 1% to 10% and the use temperature is 20 to 50°C.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the high-efficiency and environment-friendly low-temperature gel breaker for shallow oil and gas wells, the invention comprises the following steps: firstly, acrylic acid, acrylamide, sodium lignin sulfonate, polyvinyl alcohol and a cross-linking agent are polymerized and then loaded with oxalic acid to obtain a slow-release capsule core; glutaraldehyde is reacted with sodium carboxymethyl cellulose and then added to the slow-release capsule core for immersion, and then dried to obtain a catalytic slow-release capsule; and persulfate, sodium thiosulfate, sodium bisulfite formaldehyde solution, a chelating agent, sodium nitrite, ammonium chloride and a catalytic slow-release capsule are added into pure water and mixed evenly to obtain the high-efficiency and environment-friendly low-temperature gel breaker for shallow oil and gas wells.
[0018] First, acrylic acid, acrylamide, sodium lignin sulfonate, polyvinyl alcohol, and a cross-linking agent are reacted and polymerized, and then oxalic acid is loaded to prepare a sustained-release capsule core. Acrylic acid and acrylamide undergo free radical reaction through double bonds. Sodium lignin sulfonate forms a large free radical under the action of the initiator ammonium persulfate, and undergoes a grafting reaction with the polymer chain segments formed by acrylic acid and acrylamide. N,N'-methylenebisacrylamide plays the role of a cross-linking agent to form a three-dimensional network structure. At the same time, the added polyvinyl alcohol molecular chains are interspersed in the three-dimensional grid to form an interpenetrating network structure. Oxalic acid is loaded synchronously during the reaction. Oxalic acid is loaded in large quantities by forming hydrogen bonds with carboxyl, hydroxyl, amide and other groups on the molecular chain. The prepared sustained-release capsule core has a large number of hydrophilic groups such as carboxyl, sulfonic acid, hydroxyl, and amide. The invention has excellent water absorption and swelling performance. During use, sufficient water absorption can make the sustained-release capsule core fully swell, thereby opening the internal channel to release the oxalic acid molecules loaded inside. After glutaraldehyde reacts with sodium carboxymethyl cellulose, it is added to the sustained-release capsule core and impregnated therein. After drying, a catalytic sustained-release capsule is obtained. Glutaraldehyde can react with sodium carboxymethyl cellulose to form a three-dimensional network structure, providing better mechanical properties. The prepared sustained-release capsule core is added to the cross-linked sodium carboxymethyl cellulose solution and fully immersed. A layer of carboxymethyl cellulose protective shell layer can be coated on the surface of the sustained-release capsule core. This protective layer can protect the internal capsule core from damage during storage and transportation, and prevent the capsule core from absorbing water and swelling too quickly when used in the fracturing fluid, thereby achieving the effect of controlling the delayed release time of oxalic acid.
[0019] Finally, persulfate, sodium thiosulfate, sodium bisulfite formaldehyde solution, chelating agent, sodium nitrite, ammonium chloride, and catalytic sustained-release capsules are added to pure water and mixed evenly to obtain a high-efficiency and environmentally friendly low-temperature gel breaker for shallow oil and gas wells. Sodium thiosulfate and sodium bisulfite formaldehyde solution have good reducibility under low temperature conditions. The synergistic effect of the two can activate the decomposition of persulfate to produce free radicals through the redox catalytic effect within the time required for construction. This process is completed within about 4 to 5 hours. The chelating agent glucose used can chelate the residual metals in the sodium bisulfite formaldehyde solution ions to avoid affecting the reaction process, and can also serve as a reducing agent to assist in activating persulfate; in addition, sodium nitrite and ammonium chloride can undergo a self-heating reaction under acidic conditions, and the catalytic sustained-release capsule is loaded with an acidic catalyst, oxalic acid. When it is officially used, the catalytic sustained-release capsule absorbs water and begins to expand. At the same time, due to the existence of the external shell layer, it cannot fully expand at the first time, avoiding the excessive release of oxalic acid, which leads to a rapid decrease in the viscosity of the fracturing fluid and the failure of the fracturing construction. The subsequent sustained-release capsule core expands after a period of sufficient water absorption, causing the external sodium carboxymethyl cellulose layer to rupture, thereby The oxalic acid inside begins to be released. After being released, the oxalic acid begins to catalyze the self-heating system of sodium nitrite and ammonium chloride. In the formation, this self-heating system can rapidly heat the fracturing fluid to above 60°C. At this time, the added persulfate oxidant has been partially activated under the reduction catalysis of sodium thiosulfate and sodium bisulfite formaldehyde. After the temperature rises, this activation system is rapidly accelerated. The persulfate releases a large number of free radicals and begins to attack the polymer chain segments of the thickener in the fracturing fluid, breaking them into small molecules to reduce the viscosity to facilitate flowback, and forming a slow-release capsule core. The polymer network will also be oxidized and degraded into small molecules under the action of persulfate, and then recovered together with the flowback to avoid staying in the formation and causing damage to the formation. In the process of sodium carboxymethyl cellulose shell rupture and oxalic acid release from the sustained-release capsule core, the partially activated persulfate will also play its strong oxidizing role to accelerate this process. The two can cooperate with each other, so that both effects can be quickly exerted in a short time. At the same time, after the self-heating system heats up the formation, it can effectively reduce the viscosity of the formation oil storage, further improve the production capacity of subsequent oil fields, and achieve the effect of increased production. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] In all the following examples and comparative examples, ammonium persulfate was used as the persulfate.
[0022] Embodiment 1: A method for preparing an efficient and environmentally friendly low-temperature breaker for shallow oil and gas wells, the method for preparing an efficient and environmentally friendly low-temperature breaker for shallow oil and gas wells comprising the following preparation steps: (1) By weight, 20 parts of acrylic acid and 50 parts of 3 mol / L sodium hydroxide solution were mixed evenly, and then 2 parts of acrylamide were added, and stirred at 200 r / min at room temperature until completely dissolved to prepare an acrylic acid mixed solution; (2) By weight, 1 part of polyvinyl alcohol and 40 parts of pure water were mixed evenly, stirred at 85°C and 300 r / min for 60 min until dissolved, cooled to 50°C, 1 part of sodium lignin sulfonate and 0.2 part of ammonium persulfate were added, and stirring was continued for 40 min. A mixed solution of 4 parts of oxalic acid and 80 parts of acrylic acid was added, and stirring was continued for 40 min. 0.04 part of N,N'-methylenebisacrylamide was added, and the temperature was raised to 70°C, and stirred at 300 r / min for 5 h. The mixture was vacuum dried at 60°C for 20 h, and washed with ethanol for 3 times. The mixture was vacuum dried at 60°C for 6 h, and crushed and passed through a 40-mesh sieve to obtain a sustained-release capsule core; (3) In a 50°C water bath at 50 r / min, 2 parts of 1 wt% glutaraldehyde aqueous solution were added dropwise at a rate of 2 drops per second to 50 parts of 3 wt% sodium carboxymethyl cellulose aqueous solution. After the addition was completed, stirring was continued for 6 hours. The mixture was naturally cooled to room temperature. Under stirring conditions of 50 r / min, 2 parts of sustained-release capsule cores were added thereto and immersed for 20 minutes. The mixture was taken out and vacuum dried at 60°C for 18 hours to obtain catalytic sustained-release capsules. (4) By weight, 0.4 parts of ammonium persulfate, 0.075 parts of sodium thiosulfate, 0.3 parts of sodium bisulfite formaldehyde solution, 0.003 parts of a chelating agent, 8 parts of sodium nitrite, 6 parts of ammonium chloride, 0.8 parts of a catalytic sustained-release capsule, and 40 parts of pure water were mixed evenly to prepare a high-efficiency and environmentally friendly low-temperature gel breaker for shallow oil and gas wells.
[0023] Embodiment 2: A method for preparing an efficient and environmentally friendly low-temperature breaker for shallow oil and gas wells, the method for preparing an efficient and environmentally friendly low-temperature breaker for shallow oil and gas wells comprising the following preparation steps: (1) By weight, 25 parts of acrylic acid and 55 parts of 3 mol / L sodium hydroxide solution were mixed evenly, and then 2.5 parts of acrylamide were added, and stirred at 250 r / min at room temperature until completely dissolved to prepare an acrylic acid mixed solution; (2) By weight, 1.1 parts of polyvinyl alcohol and 45 parts of pure water were mixed evenly, stirred at 85°C and 350 r / min for 55 min until dissolved, cooled to 55°C, 1.1 parts of sodium lignin sulfonate and 0.3 parts of ammonium persulfate were added, and stirring was continued for 35 min. A mixed solution of 5 parts of oxalic acid and 85 parts of acrylic acid was added, and stirring was continued for 35 min. 0.05 parts of N,N'-methylenebisacrylamide was added, and the temperature was raised to 70°C, and stirred at 350 r / min for 4.5 h. The mixture was vacuum dried at 65°C for 19 h, and washed with ethanol for 4 times. The mixture was vacuum dried at 65°C for 5.5 h, and crushed and passed through a 45-mesh sieve to obtain a sustained-release capsule core; (3) In a water bath at 55°C and 75 r / min, 2.5 parts of a 1 wt% glutaraldehyde aqueous solution were added dropwise at a rate of 3 drops per second to 55 parts of a 3 wt% sodium carboxymethyl cellulose aqueous solution. After the addition was completed, stirring was continued for 5.5 hours. The mixture was naturally cooled to room temperature. Under stirring conditions of 75 r / min, 2.5 parts of sustained-release capsule cores were added thereto and immersed for 25 minutes. The mixture was taken out and vacuum dried at 65°C for 17 hours to obtain catalytic sustained-release capsules. (4) By weight, 0.45 parts of ammonium persulfate, 0.096 parts of sodium thiosulfate, 0.338 parts of sodium bisulfite formaldehyde solution, 0.0052 parts of a chelating agent, 8.5 parts of sodium nitrite, 6.5 parts of ammonium chloride, 0.9 parts of a catalytic sustained-release capsule, and 45 parts of pure water were mixed uniformly to prepare a high-efficiency and environmentally friendly low-temperature gel breaker for shallow oil and gas wells.
[0024] Embodiment 3: A method for preparing an efficient and environmentally friendly low-temperature breaker for shallow oil and gas wells, the method for preparing an efficient and environmentally friendly low-temperature breaker for shallow oil and gas wells comprising the following preparation steps: (1) By weight, 30 parts of acrylic acid and 60 parts of 3 mol / L sodium hydroxide solution were mixed evenly, and then 3 parts of acrylamide were added, and stirred at 300 r / min at room temperature until completely dissolved to prepare an acrylic acid mixed solution; (2) By weight, 1.2 parts of polyvinyl alcohol and 50 parts of pure water were mixed evenly, stirred at 90°C and 400 r / min for 50 min until dissolved, cooled to 60°C, 1.2 parts of sodium lignin sulfonate and 0.4 parts of ammonium persulfate were added, and stirring was continued for 30 min. A mixed solution of 6 parts of oxalic acid and 90 parts of acrylic acid was added, and stirring was continued for 30 min. 0.06 parts of N,N'-methylenebisacrylamide was added, and the temperature was raised to 75°C, and stirred at 400 r / min for 4 h. The mixture was vacuum dried at 70°C for 18 h, and washed with ethanol for 4 times. The mixture was vacuum dried at 70°C for 5 h, and crushed and passed through a 50-mesh sieve to obtain a sustained-release capsule core; (3) In a water bath at 60°C and 100 r / min, 3 parts of 1 wt% glutaraldehyde aqueous solution were added dropwise at a rate of 3 drops per second to 60 parts of 3 wt% sodium carboxymethyl cellulose aqueous solution. After the addition was completed, stirring was continued for 5 hours. The mixture was naturally cooled to room temperature. 3 parts of sustained-release capsule cores were added thereto and immersed for 30 minutes under stirring at 100 r / min. The mixture was taken out and vacuum dried at 70°C for 16 hours to obtain catalytic sustained-release capsules. (4) By weight, 0.5 parts of ammonium persulfate, 0.12 parts of sodium thiosulfate, 0.375 parts of sodium bisulfite formaldehyde solution, 0.0075 parts of chelating agent, 9 parts of sodium nitrite, 7 parts of ammonium chloride, 1 part of catalytic sustained-release capsules, and 50 parts of pure water were mixed evenly to prepare a high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells.
[0025] Comparative Example 1: The preparation method of the high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells in Comparative Example 1 is different from that in Example 2 in that step (3) is not performed, and step (4) is modified as follows: 0.45 parts of ammonium persulfate, 0.096 parts of sodium thiosulfate, 0.338 parts of sodium bisulfite formaldehyde solution, 0.0052 parts of chelating agent, 8.5 parts of sodium nitrite, 6.5 parts of ammonium chloride, 0.9 parts of slow-release capsule core, and 45 parts of pure water are mixed uniformly by mass to prepare a high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells. The remaining steps are the same as in Example 2.
[0026] Comparative Example 2: The preparation method of the high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells in Comparative Example 2 is different from that in Example 2 in that steps (1), (2), and (3) are not performed, and step (4) is modified as follows: 0.45 parts of ammonium persulfate, 0.096 parts of sodium thiosulfate, 0.338 parts of sodium bisulfite formaldehyde solution, 0.0052 parts of chelating agent, 8.5 parts of sodium nitrite, 6.5 parts of ammonium chloride, 0.2 parts of oxalic acid, and 45 parts of pure water are mixed uniformly by mass to prepare a high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells. The remaining steps are the same as in Example 2.
[0027] Comparative Example 3: The preparation method of the high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells in Comparative Example 3 is different from that in Example 2 in that step (4) is different, and step (4) is modified as follows: 0.45 parts of ammonium persulfate, 0.0052 parts of chelating agent, 8.5 parts of sodium nitrite, 6.5 parts of ammonium chloride, 0.9 parts of catalytic sustained-release capsules, and 45 parts of pure water are mixed uniformly by mass to prepare a high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells. The remaining steps are the same as in Example 2.
[0028] Comparative Example 4: The preparation method of the high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells in Comparative Example 4 is different from that in Example 2 in that step (4) is different, and step (4) is modified as follows: 0.45 parts of ammonium persulfate, 0.338 parts of sodium bisulfite formaldehyde solution, 0.0052 parts of chelating agent, 8.5 parts of sodium nitrite, 6.5 parts of ammonium chloride, 0.9 parts of catalytic sustained-release capsules, and 45 parts of pure water are mixed uniformly by mass to prepare a high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells. The remaining steps are the same as in Example 2.
[0029] Comparative Example 5: The preparation method of the high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells in Comparative Example 5 is different from that in Example 2 in that step (4) is different, and step (4) is modified as follows: 0.45 parts of ammonium persulfate, 0.096 parts of sodium thiosulfate, 0.0052 parts of chelating agent, 8.5 parts of sodium nitrite, 6.5 parts of ammonium chloride, 0.9 parts of catalytic sustained-release capsules, and 45 parts of pure water are mixed uniformly by mass to prepare a high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells. The remaining steps are the same as in Example 2.
[0030] Comparative Example 6: The preparation method of the high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells in Comparative Example 6 is different from that in Example 2 in that steps (1), (2), and (3) are not performed, and step (4) is modified as follows: 0.45 parts of ammonium persulfate, 0.096 parts of sodium thiosulfate, 0.338 parts of sodium bisulfite formaldehyde solution, 0.0052 parts of chelating agent, and 45 parts of pure water are mixed uniformly by mass to prepare a high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells. The remaining steps are the same as in Example 2.
[0031] Test Example 1: Gel breaking performance test: The prepared high-efficiency and environmentally friendly low-temperature gel breaker for shallow oil and gas wells was tested for its viscosity reducing effect on the fracturing fluid to evaluate its gel breaking effect. The polymer fracturing fluid formula is as follows: by mass fraction, 0.5% anionic polyacrylamide, 5% high-efficiency and environmentally friendly low-temperature gel breaker for shallow oil and gas wells, 0.5% potassium chloride, and the balance is water, which is configured into 100 ml of fracturing fluid. The viscosity is measured by a rotational viscometer and is between 18 and 21 mPa·s. The fracturing fluid is placed in a constant temperature water bath at 20°C, and the viscosity is measured at 1h, 2h, 4h, 6h, and 8h. When the viscosity is ≤5mPa·s, the gel breaking is considered to be completed. At the same time, the temperature in the system is measured and recorded. Each group of parallel experiments is conducted 5 times, and the viscosity is recorded as the maximum and minimum values. The temperature is recorded as the average temperature when the gel breaking is completed.
[0032] The anionic polyacrylamide used was purchased from Henan Yushuifeng Environmental Protection Technology Co., Ltd.
[0033] The results are shown in Table 1.
[0034] Table 1
[0035] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 6 in Table 1, it can be found that the high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells prepared by the present invention has the advantages of self-heating, thorough gel breaking, no heavy metal ion pollution, and no influence on fracturing construction.
[0036] By comparing the data in the table, it can be seen that the reducing properties of sodium thiosulfate and sodium bisulfite formaldehyde have a synergistic effect, which together produce a catalytic effect on the decomposition of ammonium persulfate and promote the degumming process. The self-heating system of sodium nitrite and ammonium chloride also plays a good role. From the temperature test, both have reached the ideal temperature. At this temperature, the viscosity of the solution can be reduced, and the decomposition of ammonium persulfate and the degumming process can be promoted. At the same time, the addition of the self-heating system alone or the use of the reduction catalytic system of sodium thiosulfate and sodium bisulfite formaldehyde alone are both poor, and the degumming time is long. The simultaneous addition of the two shortens the degumming time and accelerates the degumming efficiency. At the same time, the loading of oxalic acid on the sustained-release capsule core in the catalytic sustained-release capsule and the wrapping of the sodium carboxymethyl cellulose shell effectively delay the degumming time, ensuring the viscosity of the fracturing fluid during the fracturing construction.
[0037] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A highly efficient and environmentally friendly low-temperature breaker for shallow oil and gas wells, characterized in that: The high-efficiency and environment-friendly low-temperature gel breaker for shallow oil and gas wells is prepared by uniformly mixing, by weight, 0.4-0.5 parts of persulfate, 0.075-0.12 parts of sodium thiosulfate, 0.3-0.375 parts of sodium bisulfite formaldehyde solution, 0.003-0.0075 parts of chelating agent, 8-9 parts of sodium nitrite, 6-7 parts of ammonium chloride, 0.8-1 parts of catalytic sustained-release capsules, and 40-50 parts of pure water; The chelating agent is glucose; The catalytic sustained-release capsule is prepared by reacting glutaraldehyde with sodium carboxymethyl cellulose and then adding the reacted glutaraldehyde to the sustained-release capsule core and impregnating the core with the catalytic sustained-release capsule. Prepared after drying; The sustained-release capsule core is prepared by polymerizing acrylic acid, acrylamide, sodium lignin sulfonate, polyvinyl alcohol, and a cross-linking agent and then loading oxalic acid; The cross-linking agent is N,N'-methylenebisacrylamide.
2. The high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells according to claim 1, characterized in that: The persulfate is one of ammonium persulfate, potassium persulfate and sodium persulfate.
3. The high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells according to claim 1, characterized in that: The sustained-release capsule core is prepared according to the following process: 1-1.2 parts of polyvinyl alcohol and 40-50 parts of pure water are mixed uniformly by weight, stirred at 85-90°C and 300-400 r / min for 50-60 min until dissolved, cooled to 50-60°C, added with 1-1.2 parts of sodium lignin sulfonate and 0.2-0.4 parts of ammonium persulfate, stirred for 30-40 min, added with 4-6 parts of oxalic acid and 80-90 parts of acrylic acid mixed solution, stirred for 30-40 min, added with 0.04-0.06 parts of N,N'-methylenebisacrylamide, heated to 70-75°C, stirred at 300-400 r / min for reaction for 4-5 h, vacuum dried at 60-70°C for 18-20 h, soaked and washed with ethanol for 3-4 times, vacuum dried at 60-70°C for 5-6 h, crushed and sieved with 40-50 mesh to obtain the sustained-release capsule core.
4. The high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells according to claim 3, characterized in that: The acrylic acid mixed solution is prepared by uniformly mixing 20-30 parts of acrylic acid and 50-60 parts of 3 mol / L sodium hydroxide solution by mass, adding 2-3 parts of acrylamide, and stirring at 200-300 r / min at room temperature until the mixture is completely dissolved.
5. The high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells according to claim 1, characterized in that: The catalytic sustained-release capsules are prepared according to the following process: by weight, 2 to 3 parts of 1wt% glutaraldehyde aqueous solution are added to 50 to 60 parts of 3wt% sodium carboxymethyl cellulose aqueous solution at a rate of 2 to 3 drops per second in a water bath at 50 to 60°C and 50 to 100 r / min, stirring is continued for 5 to 6 hours after the addition is completed, and the mixture is naturally cooled to room temperature, and 2 to 3 parts of sustained-release capsule cores are added thereto under stirring conditions of 50 to 100 r / min and immersed for 20 to 30 minutes, and the mixture is taken out and vacuum dried at 60 to 70°C for 16 to 18 hours to obtain the catalytic sustained-release capsules.
6. The high-efficiency and environmentally friendly low-temperature breaker for shallow oil and gas wells according to claim 1, characterized in that: The mass fraction of the sodium bisulphite formaldehyde solution is 35%.
7. A method for using the high-efficiency and environmentally friendly low-temperature gel breaker for shallow oil and gas wells in petroleum fracturing fluid according to any one of claims 1 to 6, characterized in that: The high-efficiency and environment-friendly low-temperature gel breaker for shallow oil and gas wells is added to fracturing fluid at a mass fraction of 1% to 10% and is used at a temperature of 20 to 50°C.
Citation Information
Patent Citations
High-strength interpenetrating-polymer-network type water-absorbent resin, and preparation method thereof
CN108017751A
Preparation method of controllable long-acting slow-release scale inhibitor capsule
CN110157401A
Sustained-release dust suppression microcapsule, and preparation method and application thereof
CN111848870A
Preparation method of oil well fracturing fluids low-temp. glue breaking agent
CN1150967A
Low-temperature gel breaking fracturing fluid as well as preparation method and application thereof
CN116179178A